Rescue of fulminant Clostridioides difficile infection in a hemodialysis patient: a case report - Hiroyoshi Yanagisawa; Megumi Oshima; Keisuke Sako; Yoshinori Takahashi; Toshiaki Tokumaru; Kaho Hayashi; Megumi Ikeda; Fumitaka Yamamori; Sho Kajikawa; Daiki Hayashi; Takahiro Yuasa; Keisuke Horikoshi; et al. (Renal Replacement Therapy)
Abstract Background Clostridioides difficile infection (CDI) is a gastrointestinal condition that arises from the disruption of normal intestinal flora, often caused by antibiotics or antiacids. Fulminant CDI, characterized by shock, intestinal obstruction, and toxic megacolon, has a poor prognosis. Patients with chronic kidney disease and those on maintenance hemodialysis are at a higher risk for developing CDI, experiencing severe disease progression, and facing increased mortality. Case presentation A 70 years-old man with diabetic nephropathy undergoing maintenance hemodialysis for 2 years developed fulminant CDI. He had been on long-term antibiotic therapy for chronic pyogenic knee arthritis for 5 months. He presented with severe watery diarrhea, and stool tests confirmed CD toxins A and B. A computed tomography (CT) scan revealed toxic megacolon with pronounced intestinal edema, bowel dilatation, and massive pleural effusion. He was in shock and admitted to the intensive care unit. Treatment included massive fluid infusion, continuous vasopressor support, and regular human albumin infusions to stabilize circulation. Antibiotic therapy was initiated with oral vancomycin (2000 mg/day) and intravenous metronidazole (1500 mg/day). Advanced supportive measures included polymyxin B-immobilized fiber column direct hemoperfusion (PMX-DHP) and continuous renal replacement therapy using a cytokine adsorption column (SepXiris®). The patient’s condition gradually improved, and antimicrobial therapy was completed on day 25 of hospitalization. Follow-up computed tomography (CT) scans showed resolution of toxic megacolon, and there were no signs of CDI recurrence. The patient was eventually transferred to a rehabilitation facility. Conclusions Despite established treatments, fulminant CDI carries a high mortality rate, particularly in patients on maintenance hemodialysis, where fatal outcomes are common. This case highlights the successful management of fulminant CDI in a hemodialysis patient through a multitargeted approach, including intensive care, circulatory support with albumin monitoring, and advanced therapies such as PMX-DHP and cytokine adsorption. This report underscores the importance of comprehensive strategies in improving outcomes for high-risk patients.